Manganese superoxide dismutase is a promising target for enhancing chemosensitivity of basal-like breast carcinoma - Prem Kumar, Alan; Loo, S.; Shin, S.; Tan, Tuan zea; Eng, C.; Singh, R.; Putti, T.; Ong, C.; Salto-Tellez, M.; Goh, B.; Park, J.; Thiery, J.; et al. (Mary Ann Liebert, Inc. Publishers, 2013)
Aims: Although earlier reports highlighted a tumor suppressor role for manganese superoxide dismutase (MnSOD), recent evidence indicates increased expression in a variety of human cancers including aggressive breast carcinoma. In the present article, we hypothesized that MnSOD expression is significantly amplified in the aggressive breast carcinoma basal subtype, and targeting MnSOD could be an attractive strategy for enhancing chemosensitivity of this highly aggressive breast cancer subtype. Results: Using MDA-MB-231 and BT549 as a model of basal breast cancer cell lines, we show that knockdown of MnSOD decreased the colony-forming ability and sensitized the cells to drug-induced cell death, while drug resistance was associated with increased MnSOD expression. In an attempt to develop a clinically relevant approach to down-regulate MnSOD expression in patients with basal breast carcinoma, we employed activation of the peroxisome proliferator-activated receptor gamma (PPARγ) to repress MnSOD expression; PPARγ activation significantly reduced MnSOD expression, increased chemosensitivity, and inhibited tumor growth. Moreover, as a proof of concept for the clinical use of PPARγ agonists to decrease MnSOD expression, biopsies derived from breast cancer patients who had received synthetic PPARγ ligands as anti-diabetic therapy had significantly reduced MnSOD expression. Finally, we provide evidence to implicate peroxynitrite as the mechanism involved in the increased sensitivity to chemotherapy induced by MnSOD repression. Innovation and Conclusion: These data provide evidence to link increased MnSOD expression with the aggressive basal breast cancer, and underscore the judicious use of PPARγ ligands for specifically down-regulating MnSOD to increase the chemosensitivity of this subtype of breast carcinoma.